Gastroenterologists' Perceptions Regarding Ulcerative Colitis and Its Management: Results from a Large-Scale Survey. Issue 10 (October 2016) - Lasch, Karen; Liu, Stephen; Ursos, Lyann; Mody, Reema; King-Concialdi, Kristen; DiBonaventura, Marco; Leberman, Julie; Dubinsky, Marla
Abstract Introduction Misperceptions about ulcerative colitis (UC) may influence management strategies and limit opportunities for improving patient outcomes. This study assessed physicians' perceptions of UC, concepts of disease severity and remission, and treatment goals. Methods Gastroenterologists who typically treated ≥10 adults with UC per month were recruited for a large-scale, web-based survey. Participants were asked about their perceptions of UC (often vs. Crohn's disease [CD]), treatment goals, and medication use. Response data were evaluated via descriptive statistics and univariate and multivariable analyses. Results Gastroenterologists (N = 500) with a mean of 16.5 years (standard deviation, 8.7 years) in practice participated. In comparison to CD, survey respondents perceived UC as being easier to diagnose, having better treatment outcomes, and being associated with later prescribing of biologics. Treatment goals commonly considered to have the greatest importance included quality of life improvement (31.2% of respondents), maintenance of clinical remission (17.4%), and mucosal healing (17.4%). When respondents evaluated the performance of medication classes in achieving these goals, biologics were rated significantly higher than all other classes (P < 0.05). However, the most common drivers for the initiation of biologic therapy were the development of steroid refractoriness (66.8%) and steroid dependency (65.8%). Medication class use by UC severity was generally consistent with the traditional step-up approach to UC therapy, with biologics being used most commonly for severe UC. Conclusion These results suggest a possible disparity between treatment goals and therapeutic management in UC. An increased awareness of general UC perceptions is an important step toward a better overall understanding of the disease and, ultimately, toward improved management aligned with treatment goals. Funding This study was sponsored by the American Gastroenterological Association (AGA), and the design and conduct of the study as well as article processing charges and the open access fee for this publication were funded by Takeda Pharmaceuticals International, Inc. (TPI).